2012
DOI: 10.1007/s11856-012-0025-0
|View full text |Cite
|
Sign up to set email alerts
|

Property (β) and uniform quotient maps

Abstract: In 1999, Bates, Johnson, Lindenstrauss, Preiss and Schechtman asked whether a Banach space that is a uniform quotient of ℓp, 1 < p = 2 < ∞, must be isomorphic to a linear quotient of ℓp. We apply the geometric property (β) of Rolewicz to the study of uniform and Lipschitz quotient maps, and answer the above question positively for the case 1 < p < 2. We also give a necessary condition for a Banach space to have c0 as a uniform quotient.2010 Mathematics Subject Classification. 46B80, 46B25, 46T99.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…Regarding the stability of the asymptotic structure of infinite-dimensional Banach spaces under nonlinear quotients, it is shown how this work unifies, and extends, a series of results from [21], [9], [31], and [10]. The quantitative approach devised in this article takes full advantage of the simple observation that the quantitative theories of biLipschitz embeddings and Lipschitz quotients coincide, in a precise sense, for trees.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Regarding the stability of the asymptotic structure of infinite-dimensional Banach spaces under nonlinear quotients, it is shown how this work unifies, and extends, a series of results from [21], [9], [31], and [10]. The quantitative approach devised in this article takes full advantage of the simple observation that the quantitative theories of biLipschitz embeddings and Lipschitz quotients coincide, in a precise sense, for trees.…”
Section: Introductionmentioning
confidence: 63%
“…Lipschitz subquotients have already been implicitly touched upon (e.g. in [25], [21], [10]). A "dual" notion was considered by Mendel and Naor in [24], where given α ∈ [1, ∞) they say that X has an α-Lipschitz quotient in Y if there is a subset S ⊂ Y and a Lipschitz quotient map f : X → S such that codist(f ) ≤ α.…”
Section: Proof Of Claim 32mentioning
confidence: 99%
See 2 more Smart Citations
“…Lima and Randrianarivony [13] showed that for q > p > 1, ℓ q is not a uniform quotient of ℓ p . Their proof relies on a technical argument called "fork argument".…”
Section: Introductionmentioning
confidence: 99%